The Dilemma of Unsystematic Remedial Education Data Management - Awang, Hapini; Mansor, Nur Suhaili; Mat Yamin, Fadhilah; Yusof, Mat Rahimi; Mohd Yaakob, Mohd Faiz (2023)
The three educational officers of Unit Pemulihan Khas in Pejabat Pendidikan Daerah Cameron Highlands (PPDCH) realized their unsystematic remedial data management. At the time when this case is written (September 2020) the process of gathering remedial data is still done using the MS Excel template, which may subject to some errors. In addition, the procedure makes the officers difficult to manage the data, especially to produce customized reports. Hence, they believe that there is an urgent need to develop a computerized system that can handle all the processes of remedial data management, starting from data collection until report preparation. Therefore, this case study has investigated the issue in detail and proposed an online Remedial Data Management System. In January 2021, a prototype of the has been developed. However, this prototype was subjected to several drawbacks, especially in terms of system design. Therefore, this case is suitable to be used in the subject of System Analysis and Design.